Mitochondria Associate with P-bodies and Modulate MicroRNA-mediated RNA Interference - Huang, Lue (American Society for Biochemistry and Molecular Biology, 2011)
P-bodies are cytoplasmic granules that are linked to mRNA decay, mRNA storage, and RNA interference (RNAi). They are known to interact with stress granules in stressed cells, and with late endosomes. Here, we report that P-bodies also interact with mitochondria, as previously described for P-body-related granules in germ cells. The interaction is dynamic, as a large majority of P-bodies contacts mitochondria at least once within a 3-min interval, and for about 18 s. This association requires an intact microtubule network. The depletion of P-bodies does not seem to affect mitochondria, nor the mitochondrial activity to be required for their contacts with P-bodies. However, inactivation of mitochondria leads to a strong decrease of miRNA-mediated RNAi efficiency, and to a lesser extent of siRNA-mediated RNAi. The defect occurs during the assembly of active RISC and is associated with a specific delocalization of endogeneous Ago2 from P-bodies. Our study reveals the possible involvement of RNAi defect in pathologies involving mitochondrial deficiencies.